Characteristics of sway in the center of gravity of badminton players - Masu, Y.; Muramatsu, K.; Hayashi, N. (Journal of Physical Therapy Science, 2014)
[Purpose] To clarify the characteristics of fluctuations in the center of gravity (CoG) of badminton players by comparing them between those with high and low performance levels. [Subjects] Eight male badminton players belonging to teams ranked among the top 3 at the All Japan Badminton Championships (high-level group) and 8 playing badminton for recreation in university clubs (low-level group) were studied.